Improving Primary Education Students' Attitude to the Profession Based on a Creative Approach - To'raboyeva Mahliyo Kozimbek qizi (European Science Publishing, 2024)
Primary education serves as the foundation for a child's educational journey and their attitude towards learning is shaped greatly during this formative period. However, in recent times, there has been a perceived decline in students' enthusiasm and passion for the teaching profession at the primary level. This warrants the need for a creative approach to be adopted to help improve students' attitude and foster positive perceptions of becoming a teacher. This article explores how a creative pedagogical model can aid in developing a favourable outlook towards the teaching career amongst primary school children.
Keywords: traditional teaching, activities, future jobs, interactive methods, well-qualified teachers.